Extraskeletal myxoid chondrosarcoma in the lung: asymptomatic lung mass with severe anemia - Zhou Qianjun; Lu Guangzhong; Liu Aiqun; Kohno Tadasu (BMC, 2012)
Abstract Extraskeletal myxoid chondrosarcoma (EMC) is a rare soft-tissue sarcoma, which primarily occurs deep in the extremities, especially in skeletal muscle, or tendon. EMC of the pleura has been described, however, no case of primary EMC arising from lung has been previously reported. We describe herein, a 51-year-old Asian female initially manifested with signs of severe anemia who presented with a lung mass unrelated to pleura that was morphologically typical EMC, with strong immunoreactivity for vimentin and NSE. Two weeks after resection, the anemia was cured. The patient continued with follow-up, without sign of abnormality 32 months after operation. Virtual slides The virtual slides for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/2882199847396682